1999
DOI: 10.1021/jp9843510
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Density of Polymer Gels 1. A Pycnometry Method Applied to Poly(N-isopropylacrylamide)−Water System

Abstract: Polymer gels that are in equilibrium with excess solvent(s) are three-component systems consisting of crosslinked polymer networks, solvent(s) in gels, and solvent(s). We have developed a method for the determination of densities of the polymer and solvent components in gels by using a specifically designed pycnometer. The method was applied to the cross-linked poly(N-isopropylacrylamide) and water system from 3.0 to 50.0 °C. From the densities of the polymer and solvent components, we have evaluated the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…His measurements verified the earlier findings that the physical state of water in gels is not identical to that of the liquid water [32]. For ionic NIPA gels modified with acrylic acid groups, he found that acrylic acid residues could retain water molecules more than 9 times that of NIPA residues.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…His measurements verified the earlier findings that the physical state of water in gels is not identical to that of the liquid water [32]. For ionic NIPA gels modified with acrylic acid groups, he found that acrylic acid residues could retain water molecules more than 9 times that of NIPA residues.…”
Section: Resultssupporting
confidence: 73%
“…Tokuhiro [32] has determined the number and distribution of water molecules in 15 swollen NIPA gels by measuring the densities of those gels using a specially designed pycnometer.…”
Section: Resultsmentioning
confidence: 99%
“…has developed a new approach for the determination of the absolute values of 1) the total volume, 2) densities of the polymer and solvent components, and 3) the stoichiometry of gels. The approach has been applied to various polymer gels (T. Tokuhiro, 1999; T. Tokuhiro, 2001). This new approach can presents results at the nanoscale and thus can compare the physical property of any gel systems composed of different kinds of polymer and/or solvent (T. Tokuhiro, 2001; T. Tokuhiro, unpublished-1).…”
Section: Polymer Gel Basicsmentioning
confidence: 99%
“…Here, v sp (gel) and N s (gel) are the volume occupied by a single polymeric residue and associated water molecules and number of water molecules per a single polymeric residue, respectively. These studies have yielded the following results, namely that: 1) the volumetric contraction of gels with increasing temperature arise from the loss of water in gels and 2) the transition from the swollen to shrunken state is the result from the loss of water and the conformational changes in the polymer component (T. Tokuhiro, 1999; T. Tokuhiro, et al, 1991). Our DSC results for various hydrogels of poly[N-isopropylacrylamide (NIPA)] indicates that the above transition is an endothermic process with raising temperature (T. Tokuhiro, unpublished-2).…”
mentioning
confidence: 99%
See 1 more Smart Citation